Analisis Yuridis Kekuatan Pembuktian Perjanjian Lisan dalam Penyelesaian Sengketa Wanprestasi Berdasarkan Putusan Pengadilan No : 44/pdt.G/2025/PN.YYK - Iva Yuli Hanifah; Khoirotunnisa; Lucky Dafira Nugroho (JUSTNESS - Jurnal Hukun Politik dan Agama, 2025)
This research discusses the probative strength of oral agreements in breach of contract disputes. Oral agreements, although not written, are legally recognized under the Indonesian Civil Code. This article uses a normative juridical approach to examine the legal position of oral contracts and their evidentiary strength in courts. The findings reveal that oral agreements can be valid but have weaker evidentiary value compared to written agreements, especially in disputes involving default. Courts rely on witness testimony and supporting evidence to assess credibility. The conclusion emphasizes the need for legal awareness regarding contract documentation to prevent disputes.